Restitution in public and private law. - Jones, Gareth (Bombay, 1991)
Professor Gareth Jones was educated at the Universities of London, Cambridge and Harvard. He is a member of Lincoln's Inn and an Honorary Bencher of that society. Since 1961 he has been at the University of Cambridge, where he is now Downing Professor of the Laws of Eng land and Vice-Master of Trinity College. He has lectured extensively in the Com monwealth and the United States, and has been a Visiting Professor at the Chicago Law School since 1976. His publications include (with Lord Goff of Chieveley) the Law of Restitution, now in its third edition, the first English text on that subject, the History of the Law of Charity 1532-1827; and (with Sir William Goodhart Q.C.) Specific Performance. He is a Fellow of the British Academy, a member of the American Law Institute, Queen's Counsel and a Fellow of the University College London
Keywords: Public law